Psychometric properties of the HI-FI problem checklist in a sample of adults with neurological and neuropsychiatric disorders: factors contributing to life satisfaction after long-term disability. Issue 6 (13th March 2017) - Mitrushina, Maura; Tomaszewski, Robert
Abstract: Purpose To assess psychometric properties of the problem checklist (PCL) in a sample of individuals with neurological and neuropsychiatric disorders many years after trauma; to identify factors that impact life satisfaction and promote functional competence after long-term disability.Method Cross-sectional, interview- and assessment-based study. Participants were community-dwelling adults with disabilities resulting from neurological and neuropsychiatric disorders ( N  = 53), who participated in a pre-vocational readiness and social skills training program. The Problem Checklist from the New York University Head Injury Family Interview (PCL), a battery of self-rated and clinician-rated measures of social/emotional status, and neuropsychological tests were main outcome measures.Results PCL is a valid and reliable instrument with acceptable psychometric properties (reliability coefficients for two scales and the total score are above (0.795). Use of maladaptive coping strategies in our sample was reflected in inverse relationship between depression and denial of disability, and in the tendency to overrate self-reported symptoms by participants with acquired trauma. Considerably lower self-ratings of symptoms across all PCL scales were seen in those of our participants who live with parents.Conclusions The study offers initial support for the use of PCL as a measure of long-term functional outcome in individuals with neurological and neuropsychiatric diagnoses. The goal of rehabilitation in patients with long-term disabilities is increase in life satisfaction. Implications for Rehabilitation: An important goal of rehabilitation and training programs for individuals with long-term disabilities due to dysfunction of the central nervous system is to improve their quality of life. The HI-FI Problem Checklist (PCL) is a brief and efficient instrument for assessing functional outcomes after long-term disability. This study demonstrated acceptable psychometric properties of the PCL in a sample of 53 individuals participating in a pre-vocational training program and provided initial support for its utility for patients with various diagnoses.